MicroRNA 27a-3p Regulates Antimicrobial Responses of Murine Macrophages Infected by Mycobacterium avium subspecies paratuberculosis by Targeting Interleukin-10 and TGF-β-Activated Protein Kinase 1 Binding Protein 2 - Hussain, Tariq; Zhao, Deming; Shah, Syed Zahid Ali; Wang, Jie; Yue, Ruichao; Liao, Yi; Sabir, Naveed; Yang, Lifeng; Zhou, Xiangmei (Frontiers in Immunology, 2018)
Mycobacterium avium subspecies paratuberculosis (MAP) persistently survive and replicate in mononuclear phagocytic cells by adopting various strategies to subvert host immune response. Interleukin-10 (IL-10) upregulation via inhibition of macrophage bactericidal activity is a critical step for MAP survival and pathogenesis within the host cell. Mitogen activated protein kinase p38 (MAPK-p38) signaling cascade plays a crucial role in the elevation of IL-10 and progression of MAP pathogenesis. The contribution of miRNAs and their influence on the activation of macrophages during MAP pathogenesis is still unclear. In the current study, we found that miRNA-27a-3p (miR-27a) expression is downregulated during MAP infection both in vivo and in vitro. Moreover, miR-27a is also downregulated in TLR2 stimulated murine macrophages (RAW264.7 and BMDM). ELISA and Real-Time qRT-PCR results confirm that overexpression of miR-27a inhibited MAP induced IL-10 production in macrophages and upregulated pro-inflammatory cytokines, while miR-27a inhibitor counteracted these effects. Luciferase reporter assay results revealed that IL-10 and TAB2 are potential targets of miR-27a. In addition, we demonstrated that miR-27a negatively regulates TAB2 expression and diminishes TAB2 dependent p38/JNK phosphorylation, ultimately downregulating IL-10 expression in MAP infected macrophages. Furthermore, overexpression of miR-27a significantly inhibited the intracellular survival of MAP in infected macrophages. Our data shows that miR-27a augments antimicrobial activities of macrophages and inhibits the expression of IL-10, demonstrating that miR-27a regulates protective innate immune responses during MAP infection and can be exploited as a novel therapeutic target in the control of intracellular pathogens, including paratuberculosis.